2012
DOI: 10.1002/stem.1118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tissues Following Mesenchymal Stromal Cell Therapy in Humans Indicates Limited Long-Term Engraftment and No Ectopic Tissue Formation

Abstract: Mesenchymal stromal cells (MSCs) are explored as a novel treatment for a variety of medical conditions. Their fate after infusion is unclear, and long-term safety regarding malignant transformation and ectopic tissue formation has not been addressed in patients. We examined autopsy material from 18 patients who had received human leukocyte antigen (HLA)-mismatched MSCs, and 108 tissue samples from 15 patients were examined by PCR. No signs of ectopic tissue formation or malignant tumors of MSC-donor origin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
329
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(343 citation statements)
references
References 22 publications
(29 reference statements)
10
329
1
3
Order By: Relevance
“…Moreover, MSC-released EVs retain this biological effect, at least in part, thus rendering them an attractive tool to exploit the benefits of MSC therapy. Their ability to induce tolerogenic DCs, together with their easy procurement, their low tumorigenicity (as shown in several clinical studies [48]) and recent promising results in newonset diabetic patients [13] renders MSC therapy a promising therapeutic strategy to locally control autoimmune pancreas inflammation and halt the progression of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSC-released EVs retain this biological effect, at least in part, thus rendering them an attractive tool to exploit the benefits of MSC therapy. Their ability to induce tolerogenic DCs, together with their easy procurement, their low tumorigenicity (as shown in several clinical studies [48]) and recent promising results in newonset diabetic patients [13] renders MSC therapy a promising therapeutic strategy to locally control autoimmune pancreas inflammation and halt the progression of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Painting heparin onto MSCs, at least at the doses used in this study, did not interfere with the cells' immunosuppressive activity, as heparin-painted and mock-painted MSCs showed similar potency in inhibiting the proliferation of, and production of IFNγ by, activated T cells. Although the half-life of the painted heparin is relatively short (data not shown), given the hypothesis that MSCs work in a "hit and run" fashion in treating inflammatory diseases, 12 even a modest extension of their "hit" period before they "run" should have a significant impact on their function in vivo. Indeed, our in vivo studies showed that heparin-painted MSCs survived better in the draining lymph nodes and that they were more potent in suppressing the proliferation of activated antigen-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both human and animal studies, 5 it has been observed that most of the infused cells are first trapped in the lung, then some migrate out to other tissues and mysteriously disappear within a few days. The extremely low survival rate of administered MSCs suggests that they work in a "hit and run" fashion, 12 and therefore the initial survival and health status of the MSCs after administration are critical for their therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…9 Autopsy examinations have revealed that BM-MSCs can be detected in the lungs and lymph nodes of some patients, but at low levels. 9,17 Thus, MSCs hardly seem to engraft, but rather may mediate their function through paracrine factors before they are rejected.…”
Section: Introductionmentioning
confidence: 99%